RESPON GENERASI MILENIAL PADA KONTEN DAKWAH YOUTUBE AGUS MUHAMMAD IQDAM (ANALISIS NETNOGRAFI) - Hasyim Iskandar; Binti Amanah (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Modern communication tools have made it possible to spread da'wah via the internet more creatively and interestingly. An example is the use of YouTube by the Sabilu Taubah Ta'lim Council to spread Agus Muhammad Iqdam's preaching through the Gus Iqdam Official channel. Since its founding on April 1 2020, this channel has grown rapidly with 706 thousand subscribers and 228 videos. This assembly aims to approach street children and criminals in a carefree and non-formal atmosphere, providing a space for them to learn and strengthen their religious knowledge. To study more deeply related to this research, all data will be analyzed using the netnography analysis method, to find out and understand deeply the meaning, for example, of human practices, culture, works of art and texts, in the netnography method (Digital Ethnography Method in Modern Society), using theory from Rulli Nasrullah Virtual Ethnography Research (Communication, Culture and Sociotechnology Research on the Internet). Netnographic research was chosen because this research uses digital content objects, and intends to reveal reactions that are part of online culture that require online audience interaction on the internet. Researchers will make direct observations on the Gus Iqdam Channel by analyzing the text of the comment column which shows responses regarding his preaching via the YouTube account. This research found that the Gus Iqdam Official YouTube channel received a predominance of positive comments on preaching content with the theme "Live Video Routine Tuesday Evening Majlis Sabilu Taubah Blitar" on December 4 2023, which managed to collect 1000 comments. These comments focus on appreciation of the story of the Prophet and his morals as conveyed, as well as the involvement of entertaining artists. Gus Iqdam conducts da'wah with a unique approach tailored to the interests of the audience, featuring famous figures such as artists or public figures, and accepting all groups without discrimination. This makes the recitations attractive to local congregations and from outside the area. Gus Iqdam tries to keep the content fresh and interesting, using a relaxed and elegant appearance style. Although there are suggestions to pay more attention to audiences who do not understand Javanese, this research emphasizes the importance of paying attention to feedback from netizens to improve one's preaching and establish better communication. However, the preaching content with the theme "Harlah Ke 5 Day 1 with Denny Caknan, Ki Rudi Gareng, Abah Kirun, Cak Percil" on February 16 2024, although popular, caused controversy with many negative comments and insults. Gus Iqdam did not deactivate negative comments, which triggered mixed responses. Despite this, his content still gets a lot of support and positive comments because of Gus Iqdam's personal charm and the support of sponsors who help each of his content and events.